Calculation of compensating susceptance for a three-wire net - Yu.А. Sirotin (National Technical University "Kharkiv Polytechnic Institute", 2014)
A problem of inactive power compensation in a three-wire three-phase network under asymmetrical sinusoidal voltage is considered. An algorithm for calculating susceptance of a Δ-compensator for the total current component active power of which equals zero is introduced. Examples of calculation are given.